2005
DOI: 10.1002/eji.200425656
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐dependent activation of several human blood cell types by protamine‐condensed mRNA

Abstract: We reported that RNA condensed on protamine is protected from RNase-mediated degradation and can be used for vaccination. Here, we show that such complexes are also danger signals that activate mouse cells through a MyD88-dependent pathway. Moreover, mRNA-protamine complexes stimulate human blood cells. They strongly activate DC and monocytes, leading to TNF-a and IFN-a secretion. In addition, protamine-RNA complexes directly activate B cells, NK cells and granulocytes. The detailed analysis of the activated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 26 publications
2
156
0
1
Order By: Relevance
“…1C). We have already demonstrated that several cytokines are produced by human immune cells stimulated by protamine-RNA [19]. Here we show that IL-12 was produced by mouse splenocytes incubated with protamine-RNA (Fig.…”
Section: Several Cell Types Are Activated By Stabilized Mrnasupporting
confidence: 63%
See 3 more Smart Citations
“…1C). We have already demonstrated that several cytokines are produced by human immune cells stimulated by protamine-RNA [19]. Here we show that IL-12 was produced by mouse splenocytes incubated with protamine-RNA (Fig.…”
Section: Several Cell Types Are Activated By Stabilized Mrnasupporting
confidence: 63%
“…Condensation of in vitro transcribed mRNA to the cationic peptide protamine is another method for generating stabilized ssRNA capable of stimulating mouse DC [18] and several human cell types [19]. To determine whether protamine-mRNA stimulates cell types in mice other than DC, we incubated splenocytes for 16 h with protamine-condensed mRNA at a concentration of 20 lg/mL (10 lg RNA plus 10 lg protamine).…”
Section: Several Cell Types Are Activated By Stabilized Mrnamentioning
confidence: 99%
See 2 more Smart Citations
“…Although this naturally occurring protein is demonstrated to protect the mRNA from degradation, mRNA:protamine complexes were shown to strongly induce innate immune response [73]. Scheel et al indicate that protamine condensed mRNA stimulates the immune system through a MyD88-dependent pathway, suggesting that TLR7 and TLR8 are probably the receptors involved [74]. This immune activating capacity of protamine can be exploited for vaccination strategies, but seemed to inhibit the primary goal of mRNA delivery, i.e.…”
Section: Mrna Delivery Methodsmentioning
confidence: 99%